2015
DOI: 10.1111/add.13200
|View full text |Cite
|
Sign up to set email alerts
|

Clinical risk factors for death after release from prison in Washington State: a nested case–control study

Abstract: Background and aims While mortality rates after prison release are high, little is known about clinical risk factors for death. We sought to identify risk and protective factors for all-cause and accidental poisoning (overdose) death. Design Nested case control study of people released from prison. Setting Washington State Department of Corrections, Washington, USA. Participants Cases (699 all-cause deaths, of which 88 were among women, and 206 additional overdose deaths, of which 76 were among women) be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
44
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 51 publications
0
44
0
1
Order By: Relevance
“…In a study of 699 cases and 699 matched controls in the United States, identified risk factors for all‐cause mortality included a history of homelessness, injecting drug use, tobacco use, cirrhosis and use of psychiatric medications before release from custody. Substance use disorder treatment in prison was protective . In a similar study of 286 cases and 286 matched controls in Australia, risk factors for external causes of death included use of heroin and other opioids before incarceration, risky drinking before incarceration, use of anti‐depressants in prison and having served two or more prison sentences.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 699 cases and 699 matched controls in the United States, identified risk factors for all‐cause mortality included a history of homelessness, injecting drug use, tobacco use, cirrhosis and use of psychiatric medications before release from custody. Substance use disorder treatment in prison was protective . In a similar study of 286 cases and 286 matched controls in Australia, risk factors for external causes of death included use of heroin and other opioids before incarceration, risky drinking before incarceration, use of anti‐depressants in prison and having served two or more prison sentences.…”
Section: Introductionmentioning
confidence: 99%
“…The findings in Binswanger et al [13] also highlight the importance of interventions that go beyond prison walls to provide support as people transition from custody to the community. Release to homelessness was a risk factor for post-release death, raising important questions about the quality of transitional care provided to people leaving custody, and indeed the ethical obligations of correctional authorities to ensure that the basic survival needs of people who have been in their care will be met after release.…”
mentioning
confidence: 98%
“…In Binswanger et al, cirrhosis during incarceration was the factor associated with the greatest increase in odds of post-release death from any cause [13]. In a correctional population, some cirrhosis will be due to HCV infection subsequent to injecting drug use [14].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Between 2008 and 2014, 25%–27% of people with serious mental illness reported being arrested in their lifetime, compared with 17%–18% of those without serious mental illness (1). After release from correctional supervision, people with and without serious mental illness are at elevated risk of poor health outcomes, including poorly controlled behavioral and somatic conditions, drug overdose, and premature mortality (2,3). …”
mentioning
confidence: 99%